Differential roles of melatonin in plant‐host resistance and pathogen suppression in cucurbits. Issue 3 (6th June 2018) - Mandal, Mihir Kumar; Suren, Haktan; Ward, Brian; Boroujerdi, Arezue; Kousik, Chandrasekar
Abstract: Since the 1950s, research on the animal neurohormone, melatonin, has focused on its multiregulatory effect on patients suffering from insomnia, cancer, and Alzheimer's disease. In plants, melatonin plays major role in plant growth and development, and is inducible in response to diverse biotic and abiotic stresses. However, studies on the direct role of melatonin in disease suppression and as a signaling molecule in host‐pathogen defense mechanism are lacking. This study provides insight on the predicted biosynthetic pathway of melatonin in watermelon ( Citrullus lanatus ), and how application of melatonin, an environmental‐friendly immune inducer, can boost plant immunity and suppress pathogen growth where fungicide resistance and lack of genetic resistance are major problems. We evaluated the effect of spray‐applied melatonin and also transformed watermelon plants with the melatonin biosynthetic gene SNAT (serotonin N‐acetyltransferase) to determine the role of melatonin in plant defense. Increased melatonin levels in plants were found to boost resistance against the foliar pathogen Podosphaera xanthii (powdery mildew), and the soil‐borne oomycete Phytophthora capsici in watermelon and other cucurbits. Further, transcriptomic data on melatonin‐sprayed (1 mmol/L) watermelon leaves suggest that melatonin alters the expression of genes involved in both PAMP‐mediated (pathogen‐associated molecular pattern) and ETI‐mediated (effector‐triggered immunity) defenses. Twenty‐seven upregulated genes were associated with constitutive defense as well as initial priming of the melatonin‐induced plant resistance response. Our results indicate that developing strategies to increase melatonin levels in specialty crops such as watermelon can lead to resistance against diverse filamentous pathogens.